The Commodification of Fear on Nessie Judge's YouTube Channel - Ariefaldy*, Muhammad Ilhan; Mustiawan, Mustiawan; Hariyati, Farida (Riwayat: Educational Journal of History and Humanities, 2024)
Nessie Judge is a well-known YouTube content creator in Indonesia with more than 10 million followers. Nessie Judge offers content discussing mysterious phenomena that can arouse the public's fear of world mystery phenomena that cannot yet be solved. Many audiences are unknowingly attracted to spending their time and money to immerse themselves in content with this fear, which leads to exploitation and commodification activities. This research uses Vincent Mosco's Political Economy of Communication theory to determine what forms of commodification of fear exist on Nessie Judge's YouTube channel. This research has a critical paradigm and uses a content analysis method to process the data that has been collected and then analyze the forms of commodification that exist on Nessie Judge's YouTube channel by collecting observations of several of Nessie Judge's most watched content and its interactions with the audience in it. comments section and literature study of research on Nessie Judge. The results of this research show that this content is packaged in such a way as to arouse the audience's fear so that the content has selling value, subscribers do not realize that their fear is used as an element to enable the content creator to reap profits.